PERANCANGAN TATA LETAK PABRIK PACKAGING DENGAN METODE SYSTEMATIC LAYOUT PLANNING DAN COMPUTERIZED RELATIONSHIP LAYOUT PLANNING - Vanecia Marchella Hardinanerl; Lina Gozali; Adianto; Christhoper Robin (Jurnal Ilmiah Teknik Industri, 2025)
This research aims to improve the efficiency and productivity of the factory layout in a cardboard packaging manufacturing company. In this study, the Systematic Layout Planning (SLP) and Computerized Relationship Layout Planning (CORELAP) methods were adopted to redesign the factory layout in order to shorten distances and minimize material movement time, thereby enhancing workflow. Initially, a comprehensive analysis of the existing factory layout was conducted, identifying constraints that affect productivity. Subsequently, alternative layouts were designed using the SLP and CORELAP methods, and the results were compared to find a more efficient layout solution, considering factors such as facility distances, material flow, and space requirements for each workstation. Simulation results and calculations indicated that redesigning the factory layout using this approach led to a significant increase in operational efficiency. The selected layout resulted in a material handling cost efficiency improvement of up to 70% from the original layout, reducing daily movement distances by 24,414 meters.